Anterior convex lateral orbital wall: distinctive morphology in Apert syndrome. Issue 9 (November 2018) - Lu, X.; Forte, A.J.; Sawh-Martinez, R.; Wu, R.; Cabrejo, R.; Steinbacher, D.M.; Alperovich, M.; Alonso, N.; Persing, J.A.
Abstract: Bony malformations of the orbit and alterations to the soft tissue in Apert syndrome contribute to ophthalmic dysfunction. Recognised structural malformation of the sphenoid and ethmoid sinuses, together with corresponding deformities in the anterior and middle cranial base, are characteristic. Our aim was to explore the underlying structural components of disfigurement and the consequent development of the orbit in patients with Apert syndrome over time by studying 18 preoperative computed tomographic (CT) scans of affected patients and 36 scans from controls. Cephalometric measurements related to the orbit were collected, and analysed with Materialise software. The patients with Apert syndrome had larger than normal external orbital horizontal angles between the ages of 6 months and 2 years. The inside horizontal angle was narrower at 16.36° before 6 months, and continued to decrease into adulthood. The ethmoid and sphenoid side angles in affected patients consistently increased, starting at 7.93% and 14.68% of the external horizontal angle, respectively, during the first 6 months of age, and becoming 20.55% and 11.69%, respectively, in adulthood. In unaffected patients, both angles were less than 3% of the external horizontal angle overall. The orbital vertical angle also changed synchronously, with increasingly wide lateral orbits and shortened anteroposterior orbits. The anterior protrusion of the lateral orbital wall resulted from superior and posterior rotation of a curved, greater wing of the sphenoid, while the widened median orbital wall was caused by the widened ethmoid sinus. These resulted in bony deformities of the orbit, which predisposed to the visual impairments of Apert syndrome.